MEMBANGUN LINGKUNGAN DESA YANG BERINOVASI & KREATIF MELALUI KUKERTA DENGAN MEMANFAATKAN SDA DAN UMKM DI DESA PEDEKIK KABUPATEN BENGKALIS - Ufira Isbah; Epi Susilawati; Tia Wardani; Reni Puspita; Annisa Fadhira Rifly; Tiatil Mahfudzoh; Ressa Safitri Rahmadani; Tri Septiardi; Willi Wahyudi; Mhd Dicky Fadzhillah (JURNAL PENGABDIAN MANDIRI, 2023)
Pedekik Village is one of the villages that will be used as the location for the Real Work Lecture on Building Villages at the University of Riau in 2023. This Real Work Lecture in Pedekik Village provides direction and input ideas to the people of Pedekik Village to be able to build an innovative & creative village environment with how to utilize existing natural resources (SDA) and micro, small and medium enterprises (UMKM). Real Work Lectures or commonly called Kukerta or KKN, is an activity that is used as a form of service by lecturers and students to the village community. Kukerta in carrying out community service is based on knowledge and even experience that has been gained in the world of lectures through guidance from Field Supervisors. Kukerta's methods of service include education, socializing, practicing and asking questions according to the work program design that has been determined. The results of the Kukerta service to build the Pedekik Village village show that Kukerta students can bring about several changes in the village community environment through the work programs that have been carried out